Vector-controlled Permanent Magnet Synchronous Motor Using Indirect Matrix Converter - Abed, Zainab M.; Hassan, Turki K. (Iraqi Journal for Electrical and Electronic Engineering, 2020)
In this paper, the vector-controlled Permanent Magnet Synchronous Motor (PMSM) fed by Indirect Matrix Converter (IMC) is analyzed, designed, and simulated by using the IMC with Carrier Based Pulse Width Modulation (CBPWM). The CBPWM strategy is based on Space Vector Pulse Width Modulation (SVPWM) analysis, it is used to enhance the input current waveform, reduce the complexity of switching signals generation, and to solve the commutation problem. The traditional PMSM drive system is simulated for comparison with proposed drive system. The proposed drive system is compared to the traditional drive system using the Total Harmonic Distortion (THD). The comparison results show that the proposed drive system outperform the traditional drive system by THD different of 1/30 of input current and 1/1.5 of stator current, with high input power factor.